Problem and Project-based Learning as an Effective Environmental Education (EE) Methods: A Case of Textbook Development in Medan City Schools - Indriyani Rachman; Matsumoto Toru (Journal of Community Based Environmental Engineering and Management, 2023)
Environmental education (EE) is a tool for educating people about the environment, and EE textbooks are an essential resource for this purpose. This book was created by a group of elementary, middle, and high school teachers in the Medan City area who had yet to gain experience in textbook writing. A combination of problem and project-based learning (PBL and PjBL) by triggering teachers to develop a textbook for EE was carefully conducted. The project took three years, during which the teachers worked on conceptualizing and setting goals, selecting themes, creating the content, and designing teaching materials. Initially, the teachers conducted a poll which acted as a PBL approach to identify the most pressing environmental issues faced by the people of Medan City. This poll showed that waste management was the most crucial issue, followed by problems related to rivers, wastewater, waste disposal, and floods. The teachers then wrote chapters as a part of the PjBL approach for the EE book based on the identified issues and aligned with the EE curriculum. Over three years, the teachers tested the book with their students, evaluated the results, and revised it accordingly. The final questionnaire results showed that the experience of creating an EE book was valuable to the teachers and inspired them to consider making more EE resources in the future.